Faktor-faktor yang berhubungan dengan kejadian scabies pada remaja - M. Dimas; Anwar Arbi; Vera Nazhira Arifin (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Scabies, a skin disease caused by Sarcoptes scabiei infestation, remains a public health problem, particularly in developing countries, including Indonesia. Adolescents are vulnerable to infection due to high levels of social interaction and sharing of personal items. Purpose: To determine the factors related to the incidence of scabies in adolescents. Method: This quantitative study, with a case-control design, employed a retrospective approach. The population comprised 318 adolescents, with a sample of 152 respondents (76 cases and 76 controls) selected using the Nursalam formula. Data were collected from August 11–20, 2024, and analyzed using the Chi-square test with SPSS version 25 to examine the relationship between knowledge, personal hygiene behavior, and physical water quality with scabies incidence. Results: There was a significant association between knowledge (p=0.01; OR=0.390) and personal hygiene behavior (p=0.02; OR=0.441) and the incidence of scabies. Adolescents with poor knowledge and personal hygiene were at higher risk of developing scabies. Meanwhile, physical water quality did not show a significant association (p>0.05). Conclusion: Personal hygiene knowledge and practices play a significant role in reducing the incidence of scabies in adolescents, while physical water quality has not been shown to have an impact. Promotional and preventive efforts through health education need to be increased.   Keywords: Knowledg; Personal Hygiene Behavior; Physical Water; Scabies Incidence.   Pendahuluan: Scabies merupakan penyakit kulit akibat infestasi Sarcoptes scabiei yang masih menjadi masalah kesehatan masyarakat, terutama di negara berkembang termasuk Indonesia. Remaja rentan tertular karena tingginya interaksi sosial dan perilaku berbagi barang pribadi. Tujuan: Untuk mengetahui faktor-faktor yang berhubungan dengan kejadian scabies pada remaja. Metode: Penelitian kuantitatif dengan desain case control menggunakan pendekatan retrospektif. Populasi berjumlah 318 remaja dengan sampel 152 responden (76 kasus dan 76 kontrol) yang dipilih menggunakan rumus Nursalam. Data dikumpulkan pada 11–20 Agustus 2024 dan dianalisis menggunakan uji Chi-square dengan SPSS versi 25 untuk melihat hubungan antara pengetahuan, perilaku personal hygiene, dan kualitas fisik air dengan kejadian scabies. Hasil: Terdapat hubungan signifikan antara pengetahuan (p=0.01; OR=0.390) dan perilaku personal hygiene (p=0.02; OR=0.441) dengan kejadian scabies. Remaja dengan pengetahuan dan personal hygiene kurang baik lebih berisiko mengalami scabies. Sementara itu, kualitas fisik air tidak menunjukkan hubungan bermakna (p>0.05). Simpulan: Pengetahuan dan perilaku personal hygiene berperan penting dalam menurunkan kejadian scabies pada remaja, sedangkan kualitas fisik air tidak terbukti berpengaruh. Upaya promotif dan preventif melalui edukasi kesehatan perlu ditingkatkan.   Kata Kunci: Kejadian Scabies; Kualitas Fisik Air; Pengetahuan; Perilaku Personal Hygine.